Health Promotion and Disease Prevention Strategies in Older Adults with Intellectual and Developmental Disabilities - Carmeli, Eli; Imam, Bita (Frontiers in Public Health, 2014)
The rapid growth in the number of individuals living with Intellectual and Developmental Disabilities (IDD) along with their increased longevity present challenges to those concerned about health and well-being of this unique population. While much is known about health promotion and disease prevention in the general geriatric population, far less is known about those in older adults with IDD. Effective and efficient health promotion and disease prevention strategies need to be developed and implemented for improving the health and quality of life of older adults living with IDD. This is considered to be challenging given the continued shrinkage in the overall health care and welfare system services due to the cut in the governmental budget in some of the western countries. The ideal health promotion and disease prevention strategies for older adults with IDD should be tailored to the individuals’ health risks, address primary and secondary disease prevention and prevent avoidable impairments that cause premature institutionalization. Domains of intervention should include cognitive, mental and physical health, accommodations, workplace considerations, assistive technology, recreational activities and nutrition.